2012
DOI: 10.1152/ajprenal.00355.2011
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of cGMP-dependent protein kinase I (PKG-I) attenuates ischemia-reperfusion-induced kidney injury

Abstract: Overexpression of cGMP-dependent protein kinase I (PKG-I) attenuates ischemia-reperfusion-induced kidney injury. Am J Physiol Renal Physiol 302: F561-F570, 2012. First published December 7, 2011 doi:10.1152/ajprenal.00355.2011.-cGMP-dependent protein kinase (PKG) is a multifunctional protein. Whether PKG plays a role in ischemia-reperfusion-induced kidney injury (IRI) is unknown. In this study, using an in vivo mouse model of renal IRI, we determined the effect of renal IRI on kidney PKG-I levels and also ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 51 publications
(60 reference statements)
6
21
0
Order By: Relevance
“…The present study observed renal damage with methylene blue thus justifying importance of sGC in renal IRI. Similarly, an increase in cGMP-dependent protein kinase I level has been documented to be protective against IRI-induced renal injury [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study observed renal damage with methylene blue thus justifying importance of sGC in renal IRI. Similarly, an increase in cGMP-dependent protein kinase I level has been documented to be protective against IRI-induced renal injury [12].…”
Section: Discussionmentioning
confidence: 99%
“…The NO activates sGC that converts guanosine triphosphate (GTP) into cyclic guanosine monophosphate (cGMP) which in turn causes smooth muscle relaxation and vasodilatation. The role of cGMP has been explored in various models of renal dysfunction and increase in its level has been documented to be protective against IRI and cisplatin-induced renal injury [12].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of cGMP-dependent protein kinase I could protect against IR-induced kidney injury by inhibiting inflammation and tubular cell apoptosis (Li et al, 2012). Similarly, NO-cGMP (Choi et al, 2009) and NPR-cGMP signaling pathways (De Vito et al, 2010;Ogawa et al, 2012) are also known to protect IR injury by inhibiting apoptosis and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…PKG-I has numerous effects on the vessel wall such as vasodilation, vascular permeability, induction of platelet aggregation, and regulation of smooth muscle cell proliferation (20,30,32,45). In addition to regulating vessel wall function, our previous studies demonstrate a renal protective effect of PKG-I activation on diabetes or ischemia-reperfusion-induced kidney injury (29,52). Recently, numerous studies suggest an anti-tumor effect of cGMP/PKG signaling, including induction of tumor cell apoptosis and inhibition of metastasis (13,15,16,27,47).…”
mentioning
confidence: 83%
“…Results were normalized by 18S. Relative mRNA expression was calculated using the MyiQ system software as previously reported (29). 2) To quantify mitochondria DNA copy number, DNA was extracted from freshly frozen kidney tissues by using QIAamp DNA mini kit (Qiagen).…”
Section: Animalsmentioning
confidence: 99%